Positive electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
By using a specific positive electrode mixture layer composition with a combination of first and second polymer binders, the dispersion and filling of active material particles are enhanced, addressing the challenge of increasing density and capacity in non-aqueous electrolyte secondary batteries.
Patent Information
- Application Number
- JP2021550480
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-03
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-09-03
AI Technical Summary
Existing technologies face challenges in uniformly dispersing positive electrode active material particles with different average particle diameters and strengths, leading to limitations in increasing the density of the positive electrode in non-aqueous electrolyte secondary batteries.
A positive electrode mixture layer comprising a positive electrode active material with a specific composition (Li a Ni x Co y Me (1-x-y)O 2) and a combination of first and second polymer binders, where the second binder is between 5% to 35% by mass, enhances the dispersion and filling of the active material, allowing for higher density.
The solution enables a higher active material density in the positive electrode, resulting in improved capacity and cycle characteristics of non-aqueous electrolyte secondary batteries.
Smart Images

Figure 0007617435000002 
Figure 0007617435000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are used for applications such as ICT applications such as personal computers and smartphones, vehicle applications, and power storage applications. In these applications, non-aqueous electrolyte secondary batteries are required to have a higher capacity. One method for increasing the capacity of non-aqueous electrolyte secondary batteries is to densify the positive electrode active material in the positive electrode.
[0003] Patent Document 1 proposes a positive electrode for a lithium secondary battery, which includes a positive electrode active material layer containing a large particle size active material with an average particle size of 1 μm to 20 μm and a small particle size active material with an average particle size of 5 nm to 100 nm, and has an active material filling rate of 80% or more.
[0004] Patent Document 2 proposes a nonaqueous electrolyte secondary battery that contains, as a positive electrode active material, layered lithium transition metal oxide particles A and spinel lithium transition metal oxide particles B in a specific weight ratio range, and the particle size distribution of the positive electrode active material has a peak due to particle A and a peak due to particle B in the range of 1 to 50 μm, and in the volume-standard particle size distribution, the particle size (D50) of particle A and the particle size (D50) of particle B satisfy a specific formula, and the particle size (D95) of particle A and the particle size (D95) of particle B satisfy a specific formula.
[0005] Patent Document 3 discloses a compound of the general formula Li p Ni x Co y Mn z M q F aThe present invention proposes the use of a positive electrode active material powder containing, in a specific weight ratio range, a first granular powder having an average particle size D50 of 3 to 15 μm and a compressive fracture strength of 50 MPa or more, and a second granular powder having a compressive fracture strength of less than 40 MPa, the first granular powder being formed by the aggregation of a large number of fine particles of a lithium composite oxide represented by the formula: [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-146788 A [Patent Document 2] International Publication No. 2014 / 041793 [Patent Document 3] International Publication No. 2005 / 020354 Summary of the Invention
[0007] In Patent Documents 1 and 2, the control of particle size is complicated. In addition, when positive electrode active material particle groups having different average particle sizes are used, the dispersion state is likely to become non-uniform. When positive electrode active material particle groups having different strengths are used as in Patent Document 3, the types of positive electrode active materials to be combined are limited.
[0008] It is believed that if the positive electrode active material particles can be pulverized when producing a positive electrode for a non-aqueous electrolyte secondary battery, the density of the positive electrode active material can be increased without using positive electrode active material particle groups having different average particle sizes or positive electrode active material particle groups having different strengths.
[0009] One aspect of the present disclosure is a positive electrode mixture layer, the positive electrode mixture layer includes a positive electrode active material, a first binder, and a second binder, The positive electrode active material is represented by the following formula (1): Li a Ni x Co y Me (1-x-y) O2(1) (wherein 0.97≦a≦1.2, 0.5≦x≦1, and 0≦y≦0.1, and the element Me includes at least one selected from the group consisting of Al, Mn, B, W, Sr, Mg, Mo, Nb, Ti, Si, and Zr.) The composite oxide represented by the first binder is a polymer binder containing at least vinylidene fluoride units; the second binder is a polymer binder containing at least a diene unit; The present invention relates to a positive electrode for a non-aqueous electrolyte secondary battery, wherein a proportion of the second binder in the total amount of the first binder and the second binder is 5 mass % or more and 35 mass % or less.
[0010] Another aspect of the present disclosure relates to a non-aqueous electrolyte secondary battery including the above positive electrode, a negative electrode, and a lithium ion conductive non-aqueous electrolyte.
[0011] In the positive electrode of the nonaqueous electrolyte secondary battery, a high density of the positive electrode active material can be ensured. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a vertical cross-sectional view that illustrates a schematic diagram of a nonaqueous electrolyte secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] A positive electrode for a non-aqueous electrolyte secondary battery according to an embodiment of the present disclosure includes a positive electrode mixture layer. The positive electrode typically includes a positive electrode mixture layer and a positive electrode current collector. The positive electrode mixture layer includes a positive electrode active material, a first binder, and a second binder.
[0014] The positive electrode active material is represented by the following formula (1): Li a Ni x Co y Me (1-x-y) O2(1) (wherein 0.97≦a≦1.2, 0.5≦x≦1, and 0≦y≦0.1, and the element Me includes at least one selected from the group consisting of Al, Mn, B, W, Sr, Mg, Mo, Nb, Ti, Si, and Zr.) Hereinafter, the composite oxide represented by formula (1) may be referred to as oxide (1).
[0015] The first binder is a polymer binder containing at least vinylidene fluoride units. The second binder is a polymer binder containing at least diene units. The proportion of the second binder in the total amount of the first binder and the second binder is 5% by mass or more and 35% by mass or less. In this specification, the diene units in the second binder include hydrogenated products of the diene units.
[0016] Particles of the oxide (1) tend to have a relatively large compressive fracture strength. Such particles are difficult to pulverize when forming the positive electrode mixture layer, so there is a limit to high packing in the positive electrode mixture layer. According to the present disclosure, when using a positive electrode active material containing the oxide (1) as described above, the first binder and the second binder are used in a specific ratio. By using the first binder and the second binder in a specific ratio, the dispersion state of the first binder in the positive electrode mixture can be appropriately controlled, and the ratio of the crystalline part of the first binder can be increased. Since the crystalline part of the first binder has rigidity, the friction coefficient of the positive electrode mixture can be appropriately increased. The positive electrode mixture layer is formed by applying pressure to the positive electrode mixture. Therefore, the stress accompanying the pressure application of the positive electrode mixture is easily applied to the particles of the oxide (1) when forming the positive electrode mixture layer, and the particles are easily cracked. As a result, the positive electrode active material can be highly packed in the positive electrode mixture layer, so that the active material density in the positive electrode can be increased.
[0017] In both cases where the proportion of the second binder in the total amount of the first binder and the second binder exceeds 35% by mass and is less than 5% by mass, the friction coefficient of the positive electrode mixture layer is low, making it difficult to increase the active material density in the positive electrode mixture layer. If the proportion of the second binder exceeds 35% by mass, the dispersion state of the first binder cannot be maintained appropriately, and the crystallinity and rigidity of the first binder decrease, so that the friction coefficient of the positive electrode mixture layer decreases. In addition, if the proportion of the second binder is less than 5% by mass, the influence of the physical properties due to the first binder is dominant, and the effect of adding the second binder is hardly obtained.
[0018] The proportion of the second binder is 35% by mass or less, and may be 34% by mass or less.The proportion of the second binder is 5% by mass or more, and may be 8% by mass or more.
[0019] The total amount of the first binder and the second binder in the positive electrode mixture layer is, for example, 0.1 mass% or more, and preferably 0.4 mass% or more. The total amount of the first binder and the second binder is, for example, 3 mass% or less, and preferably 1.5 mass% or less. When the total amount of the first binder and the second binder is in such a range, it is possible to ensure high capacity while ensuring higher packing of the positive electrode active material.
[0020] The composition of oxide (1) is: Full discharge This is the composition of the positive electrode of a nonaqueous electrolyte secondary battery at the time of charging and discharging. In the oxide (1), the value a, which indicates the molar ratio of lithium, increases and decreases during charging and discharging.
[0021] The fully charged state refers to a state in which the battery is charged to a state of charge (SOC) of 0.98×C or more, where the rated capacity of the battery is C. The composition of oxide (1) at the fully charged state is determined by removing the positive electrode from the fully charged battery, washing it with ethyl methyl carbonate (EMC), and drying it. More specifically, a predetermined amount of positive electrode mixture is taken from the dried positive electrode, and the composition of oxide (1) can be determined by quantitatively analyzing the elements by inductively coupled plasma atomic emission spectrometry.
[0022] The friction coefficient of the positive electrode mixture layer is preferably 0.3 or more, and may be 0.31 or more. When the friction coefficient of the positive electrode mixture layer is in such a range, a state in which the particles of the oxide (1) have low slipperiness in the positive electrode mixture can be ensured. Therefore, when forming the positive electrode mixture layer, the particles of the oxide (1) can be more easily pulverized. The friction coefficient of the positive electrode mixture layer is preferably 0.5 or less, and may be 0.4 or less. When the friction coefficient of the positive electrode mixture layer is in such a range, an appropriate slipperiness of the particles of the oxide (1) can be ensured, and the particles are easily arranged in the positive electrode mixture layer, which is advantageous in terms of highly filling the positive electrode active material in the positive electrode mixture layer.
[0023] In this specification, the friction coefficient of the positive electrode mixture layer means the static friction coefficient. The friction coefficient of the positive electrode mixture layer is measured in accordance with the friction coefficient test method for plastic films and sheets of JIS K 7125:1999. The friction coefficient of the positive electrode mixture layer is measured for a positive electrode before assembling a non-aqueous electrolyte secondary battery, or for a positive electrode mixture layer of a positive electrode removed from a non-aqueous electrolyte secondary battery, washed with EMC, and dried. The friction coefficient is measured, for example, using a precision universal testing machine (AUTOGRAPH AG-X plus) manufactured by Shimadzu Corporation.
[0024] Thus, according to the present disclosure, the particles of oxide (1) can be highly packed in the positive electrode mixture layer, so that the density of the positive electrode active material can be increased. More specifically, the density of the positive electrode active material in the positive electrode mixture layer can be increased to, for example, 3.67 g / cm 3 or more (preferably 3.68 g / cm 3 Although there is no particular upper limit on the density of the positive electrode active material, from the viewpoint of easily securing high cycle characteristics, the density of the positive electrode active material is preferably 3.75 g / cm 3 It may be the following.
[0025] The density of the positive electrode active material in the positive electrode mixture layer can be determined by the following procedure for the positive electrode before assembling the non-aqueous electrolyte secondary battery, or for the positive electrode mixture layer of the positive electrode removed from the non-aqueous electrolyte secondary battery, washed with EMC, and dried. The thickness of the positive electrode mixture layer is measured for a relatively flat area of the positive electrode mixture layer, excluding the lead connection portion, etc., measuring 50 mm in length x 50 mm in width. The apparent volume of the positive electrode mixture layer in this area is determined from the length, width, and thickness. The positive electrode mixture in this area is peeled off from the positive electrode current collector, and the elements are quantitatively analyzed by inductively coupled plasma optical emission spectrometry or atomic absorption spectrometry to determine the mass of the positive electrode active material. The density of the positive electrode active material in the positive electrode mixture layer is determined by dividing this mass by the apparent volume.
[0026] From the viewpoint of ensuring a higher capacity, the ratio x of Ni in the oxide (1) may be 0.8≦x≦1. Moreover, if the ratio of Ni is large, the particles are less likely to be pulverized when forming the positive electrode mixture layer. According to the present disclosure, as described above, by using the first binder and the second binder in a specific ratio, the particles of the positive electrode active material containing the oxide (1) are more likely to be pulverized. Therefore, even in the case of 0.8≦x≦1, the particles of the oxide (1) can be easily pulverized, and the positive electrode active material can be highly filled in the positive electrode mixture layer.
[0027] From the viewpoint of easily ensuring higher thermal stability of the oxide (1), it is preferable that the element Me in the oxide (1) contains at least Al. In addition, when the element Me contains Al, the particles of the oxide (1) are not easily pulverized when forming the positive electrode mixture layer. According to the present disclosure, by using the first binder and the second binder in a specific ratio, the particles of the positive electrode active material containing the oxide (1) are easily pulverized. Therefore, even when the element Me contains at least Al, the particles of the oxide (1) can be easily pulverized, and the positive electrode active material can be highly filled in the positive electrode mixture layer.
[0028] When the element Me contains at least Al, the ratio y of Co may be 0.01≦y. In this case, the compressive fracture strength of the particles of the oxide (1) can be increased, and the efficiency of particle refinement can be improved. From the viewpoint of cost reduction, it is preferable to set y≦0.05.
[0029] When Me contains Al, it may further contain Mn. In this case, since the increase in the compressive fracture strength of the particles of the oxide (1) can be suppressed, it becomes easier to further refine the particles. The atomic ratio of Mn to Al (=Mn / Al) is preferably 0.9 or less. In this case, it is easy to ensure higher capacity and cycle characteristics. In addition, it is easy to stabilize the crystal structure of the oxide (1). The Mn / Al ratio may be 0.7 or less. From the viewpoint of easily ensuring high thermal stability, the Mn / Al ratio is preferably 0.4 or more.
[0030] The configuration of the nonaqueous electrolyte secondary battery will be described in more detail below.
[0031] (positive electrode) The positive electrode includes a positive electrode mixture layer. The positive electrode typically includes a positive electrode current collector that holds the positive electrode mixture layer. The positive electrode mixture layer may be formed on one surface or both surfaces of the positive electrode current collector.
[0032] The positive electrode current collector may be, for example, a metal foil. Examples of metals constituting the positive electrode current collector include aluminum (Al), titanium (Ti), alloys containing these metal elements, and stainless steel.
[0033] The positive electrode mixture layer contains a positive electrode active material, a first binder, and a second binder as essential components, and may contain, as optional components, a conductive agent, an additive, etc. As the additive, for example, a known material can be used.
[0034] The positive electrode active material includes an oxide (1). The oxide (1) includes a layered rock salt type crystal structure. The oxide (1) has a high Ni ratio, which is advantageous for increasing capacity and reducing costs. In addition, the oxide (1) includes Co, which is advantageous for extending the life of the battery.
[0035] In the oxide (1), the element Me is preferably at least one selected from the group consisting of Al, Mn, W, Mg, Mo, Nb, Ti, Si, and Zr. Note that Mn, W, Nb, Mg, Zr, etc. are considered to contribute to stabilizing the crystal structure.
[0036] In the oxide (1), the atomic ratio Co / Al may be set to 0 to 1.0.
[0037] The positive electrode active material may contain oxides other than the oxide (1). Examples of the other oxides include Li α CoO2, Li α NiO2, Li α MnO2, Li α Co β M 1-β O γ (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Cu, Zn, Al, Cr, Pb, Sb and B), LiMPO 4、 (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb and B). Here, 0<α≦1.1, 0≦β≦0.9 and 2≦γ≦2.3. The α value, which indicates the molar ratio of lithium, increases and decreases with charge and discharge. The composition of these oxides is, as in the case of oxide (1), as follows: Full discharge The composition at time.
[0038] The proportion of the oxide (1) in the entire positive electrode active material is, for example, 50 mass % or more, and may be 80 mass % or more, or 90 mass % or more. The positive electrode active material may be composed of only the oxide (1).
[0039] The positive electrode mixture layer contains at least a first binder and a second binder as binders. The positive electrode mixture may contain a third binder other than the first binder and the second binder.
[0040] The first binder is a polymer binder containing at least vinylidene fluoride (VDF) units. Examples of the first binder include polyvinylidene fluoride (PVDF), copolymers containing VDF units and comonomer units, and the like. Examples of the copolymers include copolymers of VDF and at least one selected from the group consisting of olefin units and halogenated olefin units. Examples of the olefins include ethylene and propylene. Examples of the halogenated olefins include olefins having at least one of fluorine and chlorine. The halogenated olefins may be, for example, perfluoroolefins. Examples of the perfluoroolefins include tetrafluoroethylene and hexafluoropropylene. However, these comonomers are merely examples and are not limited thereto.
[0041] The proportion of VDF units in the VDF copolymer is, for example, 50 mol % or more, and may be 80 mol % or more.
[0042] The second binder contains a diene unit. Examples of the diene unit include a conjugated diene unit, a non-conjugated diene unit, or a hydrogenated product thereof. The second binder preferably contains at least a conjugated diene unit or a hydrogenated product thereof. Examples of the conjugated diene unit include a butadiene unit, an isoprene unit, a pentadiene unit, or a substitution product thereof. Examples of the butadiene unit include a 1,3-butadiene unit, a 2,3-dimethyl-1,3-butadiene unit, or the like. The second binder may contain one or more types of diene units.
[0043] The second binder may contain other comonomer units other than the diene unit. Examples of other comonomer units in the second binder include vinyl cyanide units, acrylic monomers, α,β-unsaturated carboxylic acids or their anhydrides, vinyl monomers, allyl monomers, and olefins. Examples of vinyl cyanide units include acrylonitrile and methacrylonitrile. Examples of acrylic monomers include acrylic acid, methacrylic acid, acrylic acid esters, methacrylic acid esters, acrylic acid amides, and methacrylic acid amides. Examples of α,β-unsaturated carboxylic acids include α,β-unsaturated carboxylic acids other than acrylic acid and methacrylic acid. Examples of such unsaturated carboxylic acids include maleic acid and fumaric acid. Examples of vinyl monomers include vinyl esters, vinyl ethers, aromatic vinyl compounds or their halides, and vinyl halides. Examples of allyl monomers include allyl esters and allyl ethers. Examples of olefins include ethylene, propylene, and their halides. Examples of the halides of vinyl monomers (including vinyl halides) and olefin halides include fluorides and chlorides. The other comonomers may have a substituent. Examples of the substituent include, but are not limited to, a hydroxy group, a hydroxyalkyl group, an alkoxy group, a carboxy group, an alkoxycarbonyl group, an acyl group, a sulfonic acid group, a sulfonic acid ester group, a phosphonic acid group, a phosphoric acid ester group, a phosphonic acid ester group, an amino group, an alkylamino group, and an acylamino group. These other comonomers are merely examples and are not limited to these. The second binder may contain one or more types of other comonomer units.
[0044] Examples of the third binder include fluororesin, polyolefin resin, polyamide resin, polyimide resin, acrylic resin, vinyl resin, polyvinylpyrrolidone, polyethersulfone, and rubber particles. However, the third binder is different from the first binder and the second binder. The positive electrode mixture layer may contain one type of the third binder, or two or more types.
[0045] The total amount of the first binder and the second binder in the entire binder contained in the positive electrode mixture layer may be, for example, 50 mass% or more, 80 mass% or more, or 90 mass% or more. The entire binder contained in the positive electrode mixture layer may be composed of only the first binder and the second binder.
[0046] As the conductive agent, for example, a known one can be used. As the conductive agent, carbon black, conductive fiber, and carbon fluoride are exemplified. As the carbon black, for example, acetylene black is exemplified. As the conductive fiber, carbon fiber, metal fiber, etc. are exemplified. Carbon fiber also includes carbon nanotubes. The positive electrode mixture layer may contain one type of conductive agent, or may contain two or more types.
[0047] The positive electrode mixture layer can be formed by applying a positive electrode slurry, which is a positive electrode mixture containing a positive electrode active material, a binder, a conductive agent, etc., dispersed in a dispersion medium, to the surface of a positive electrode current collector and drying the coating. After drying, the coating is usually compressed in the thickness direction of the coating.
[0048] In order to prevent stress from being applied to the positive electrode active material particles when the positive electrode mixture layer is formed, the positive electrode active material used in the positive electrode slurry preferably has an average particle size of 10 μm or more.In order to facilitate cost reduction, the positive electrode active material used in the positive electrode slurry preferably has an average particle size of 13 μm or less.
[0049] The average particle size of the positive electrode active material used in the positive electrode slurry means the particle size at which the volume integrated value is 50% in the particle size distribution measured by the laser diffraction scattering method (in other words, the volume average particle size).
[0050] (Negative electrode) The negative electrode includes, for example, a negative electrode mixture layer containing a negative electrode active material, and a negative electrode current collector supporting the negative electrode mixture layer. The negative electrode active material includes at least a carbon material that absorbs and releases lithium ions.
[0051] The negative electrode current collector may be, for example, a metal foil. The metal constituting the negative electrode current collector is preferably a metal that does not react with lithium metal, such as copper, nickel, iron, and alloys containing these metal elements.
[0052] The negative electrode mixture layer can be formed, for example, by applying a negative electrode slurry in which the negative electrode mixture is dispersed in a dispersion medium to the surface of the negative electrode current collector and drying it. The coating film after drying may be rolled as necessary. The negative electrode mixture layer may be formed on one surface or both surfaces of the negative electrode current collector.
[0053] The negative electrode mixture contains a negative electrode active material as an essential component, and may contain a binder, a conductive agent, a thickener, and the like as optional components. For example, known materials can be used as the binder, the conductive agent, and the thickener. The binder may be selected from the first to third binders exemplified for the positive electrode mixture layer. The conductive agent may be selected from those exemplified for the positive electrode mixture layer. In addition, the negative electrode active material contains a carbon material that absorbs and releases lithium ions as an essential component.
[0054] Examples of carbon materials that absorb and release lithium ions include graphite, graphitizable carbon, and non-graphitizable carbon. Graphitizable carbon is sometimes called soft carbon. Non-graphitizable carbon is sometimes called hard carbon. Among them, graphite is preferable because it has excellent charge / discharge stability and low irreversible capacity. The negative electrode active material may contain a material other than a carbon material. It is preferable that 80% by mass or more or 90% by mass or more of the negative electrode active material is graphite.
[0055] Graphite is a carbon material with a developed graphite crystal structure, and may be, for example, graphite having a (002) plane interplanar spacing d002 of 3.4 Å or less as measured by X-ray diffraction. The graphite crystallite size may be 100 Å or more. The crystallite size is measured, for example, by the Scherrer method.
[0056] Materials other than carbon materials that can be used as negative electrode active materials include alloy materials, which are materials that contain at least one metal capable of forming an alloy with lithium, such as silicon, tin, silicon alloys, tin alloys, and silicon compounds.
[0057] The alloy-based material may be a composite material having a lithium ion conductive phase and silicon particles dispersed in the phase. The lithium ion conductive phase may be a silicate phase or a silicon oxide phase containing 95% or more by mass of silicon dioxide.
[0058] (Non-aqueous electrolyte) The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the non-aqueous electrolyte is, for example, 0.5 to 2 mol / L. The non-aqueous electrolyte may contain known additives.
[0059] As the non-aqueous solvent, for example, a cyclic carbonate ester, a chain carbonate ester, a cyclic carboxylate ester, etc. are used. As the cyclic carbonate ester, propylene carbonate, ethylene carbonate, etc. are listed. As the chain carbonate ester, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, etc. are listed. As the cyclic carboxylate ester, γ-butyrolactone, γ-valerolactone, etc. are listed. As the non-aqueous solvent, one type may be used alone, or two or more types may be used in combination.
[0060] Examples of the lithium salt include lithium salts of chlorine-containing acids, lithium salts of fluorine-containing acids, lithium salts of fluorine-containing acid imides, and lithium halides. Examples of the lithium salts of chlorine-containing acids include LiClO4, LiAlCl4, LiB10 Cl 10 Examples of the lithium salt of a fluorine-containing acid include LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, and LiCF3CO2. Examples of the lithium salt of a fluorine-containing acid imide include LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), and LiN(C2F5SO2)2. Examples of the lithium halide include LiCl, LiBr, and LiI. The lithium salt may be used alone or in combination of two or more.
[0061] (Separator) A separator may be interposed between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.
[0062] (Nonaqueous electrolyte secondary battery) The type and shape of the nonaqueous electrolyte secondary battery are not particularly limited. For example, they can be appropriately selected from various shapes such as a cylindrical type, a coin type, a square type, a sheet type, a flat type, etc. The form of the electrode group is also not particularly limited, and may be, for example, a wound type, a laminated type, etc.
[0063] As an example, FIG. 1 shows a longitudinal cross-sectional view of a cylindrical non-aqueous electrolyte secondary battery. The non-aqueous electrolyte secondary battery 100 includes a wound electrode group 40 and a non-aqueous electrolyte (not shown). The electrode group 40 includes a strip-shaped positive electrode 10, a negative electrode 20, and a separator 30. A positive electrode lead 13 is connected to the positive electrode 10, and a negative electrode lead 23 is connected to the negative electrode 20. One end of the positive electrode lead 13 in the length direction is connected to the positive electrode 10, and the other end is connected to a sealing plate 90. The sealing plate 90 is provided with a positive electrode terminal 15. One end of the negative electrode lead 23 is connected to the negative electrode 20, and the other end is connected to the bottom of a battery case 70 that serves as a negative electrode terminal. The battery case (battery can) 70 is made of metal, for example, iron. An upper insulating ring 80 and a lower insulating ring 60 made of resin are arranged above and below the electrode group 40, respectively. In the illustrated example, a cylindrical battery including a wound electrode group has been described, but the present embodiment can be applied to other cases as well.
[0064] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0065] Examples 1 to 3 and Comparative Example 1 A lithium nickel composite oxide, which is a positive electrode active material, a binder, acetylene black, and N-methyl-2-pyrrolidone (NMP) were mixed in a predetermined mass ratio to prepare a positive electrode slurry. As the binder, polyvinylidene fluoride was used as the first binder, and modified butadiene rubber (containing acrylonitrile units) was used as the second binder. The ratio of the second binder to the total amount of the first binder and the second binder was set to the value shown in Table 1. The ratio of the total amount of the first binder and the second binder to the solid content of the positive electrode slurry (in other words, the positive electrode mixture layer) was set to 1 mass%. As the lithium nickel composite oxide, NCA1 (LiNi 0.9 Co 0.05 Al 0.05 O2, D50: 12 μm) or NCA2 (LiNi 0.9 Co 0.04 Al 0.06 O2, D50: 12 μm) was used.
[0066] The positive electrode slurry was applied to both surfaces of an aluminum foil serving as a positive electrode current collector, the coating was dried, and then the aluminum foil was rolled to form a positive electrode mixture layer on both surfaces of the aluminum foil, thus producing a positive electrode for a non-aqueous electrolyte secondary battery.
[0067] Comparative Examples 2 and 3 A positive electrode was produced in the same manner as in Example 1 or Example 3, except that the second binder was not used.
[0068] "evaluation" (1) Friction coefficient The friction coefficient on the surface of the positive electrode mixture layer of the positive electrode was determined by the procedure already described. (2) Cathode active material density The density of the positive electrode active material in the positive electrode was determined by the procedure already described.
[0069] The results are shown in Table 1. In Table 1, E1 to E3 are Examples 1 to 3, and R1 to R3 are Comparative Examples 1 to 3.
[0070] [Table 1]
[0071] As shown in Table 1, when the proportion of the second binder was less than 5 mass% or more than 35 mass%, the friction coefficient of the positive electrode mixture layer was low and the positive electrode active material density was also low. In contrast, in the positive electrodes of the examples in which the proportion of the second binder was 5 mass% or more and 35 mass% or less, the friction coefficient of the positive electrode mixture layer was larger than that of the comparative examples, and the positive electrode active material density was improved.
[0072] 《Nonaqueous electrolyte secondary battery》 A non-aqueous electrolyte secondary battery was fabricated using the positive electrode fabricated in the example. The non-aqueous electrolyte secondary battery was fabricated in the following manner. (1) Preparation of the negative electrode Artificial graphite (average particle size 30 μm), acetylene black, and polyvinylidene fluoride were mixed in a predetermined mass ratio, and NMP was added to prepare a negative electrode slurry. Next, the negative electrode slurry was applied to the surface of an electrolytic copper foil serving as a negative electrode current collector, and the coating was dried and then rolled to form a negative electrode mixture layer on both sides of the copper foil. (2) Preparation of non-aqueous electrolyte A non-aqueous electrolyte solution was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate and diethyl carbonate in a volume ratio of 3:7. (3) Assembly of non-aqueous electrolyte secondary battery Lead tabs were attached to the positive and negative electrodes, respectively, and the positive and negative electrodes were spirally wound with a separator between them so that the leads were located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an exterior body made of a laminate film with an aluminum foil as a barrier layer, and vacuum dried at 105°C for 2 hours. After that, an electrolyte was poured in and the opening of the exterior body was sealed to obtain a nonaqueous electrolyte secondary battery.
[0073] When the obtained nonaqueous electrolyte secondary battery was charged and discharged, a high capacity corresponding to the density of the positive electrode active material was obtained. [Industrial Applicability]
[0074] Since the nonaqueous electrolyte secondary battery including the positive electrode according to the present disclosure has a high capacity, it can be used in electronic devices such as mobile phones, smartphones, and tablet terminals, electric vehicles including hybrids and plug-in hybrids, and home storage batteries combined with solar cells. [Explanation of symbols]
[0075] 10 positive electrode 13 Positive lead 15 Positive terminal 20 negative electrode 23 Negative lead 30 Separator 40 electrode groups 60 Lower insulation ring 70 Battery case 80 Upper insulation ring 90 Sealing plate 100 Non-aqueous electrolyte secondary battery
Claims
1. A positive electrode mixture layer is provided, The positive electrode mixture layer includes a positive electrode active material, a first binder, and a second binder, The positive electrode active material has the following formula (1): Li a Ni x Co y Me (1-x-y) O 2 (1) (Here, 0.97≦a≦1.2, 0.5≦x≦1, and 0≦y≦0.1, and the element Me includes at least one selected from the group consisting of Al, Mn, B, W, Sr, Mg, Mo, Nb, Ti, Si, and Zr.) The composite oxide represented by the first binder is a polymer binder containing at least vinylidene fluoride units; the second binder is a polymer binder containing at least a diene unit; A ratio of the second binder to a total amount of the first binder and the second binder is 5% by mass or more and 35% by mass or less, The positive electrode for a non-aqueous electrolyte secondary battery, wherein the positive electrode mixture layer has a coefficient of friction of 0.3 or more and 0.5 or less.
2. 2 . The positive electrode for a nonaqueous electrolyte secondary battery according to claim 1 , wherein a ratio of a total amount of the first binder and the second binder in the positive electrode mixture layer is 0.4 mass % or more and 1.5 mass % or less.
3. 3. The positive electrode for a non-aqueous electrolyte secondary battery in accordance with claim 1, wherein 0.8≦x≦1 is satisfied.
4. 4. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the Me contains at least Al.
5. The positive electrode for a nonaqueous electrolyte secondary battery according to claim 4 , wherein 0.01≦y≦0.05 is satisfied.
6. The Me further contains Mn, 6. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 4, wherein an atomic ratio of Mn to Al is 0.9 or less.
7. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the proportion of said composite oxide in the total positive electrode active material exceeds 50 mass %.
8. A non-aqueous electrolyte secondary battery comprising the positive electrode according to any one of claims 1 to 7, a negative electrode, and a lithium ion conductive non-aqueous electrolyte.
Citation Information
Patent Citations
Coating liquid for positive electrode formation for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery
JP2009146788A
Positive electrode for lithium-ion secondary battery, and lithium-ion secondary battery using the same
JP2010033924A
Negative electrode for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
JP2018120706A
Positive electrode active material powder for lithium secondary battery
WO2005020354A1
Nonaqueous electrolyte secondary battery
WO2014041793A1